Strengthening Employer Engagement in CTEVT Technical Schools: Some Practices and Initiatives - Shrestha, Rajendra Bahadur (Journal of Technical and Vocational Education and Training, 2022)
Developing engagements with private sector at all levels of the training programs facilitates the development of workable solutions for school-to-work transitions. Employer engagement in Technical and Vocational Education and Training (TVET) system covers a spectrum of cooperation and involves small participation to build the trust required to develop more robust long-term engagement strategies. Engagement of employer is an essential component of overall training programs. It leads to developing responsive labour market skill needs, supporting priority economic sectors, training design and development, training delivery and post training support to develop ongoing dialogue with employer and employer associations. The employer has a crucial role to play in the overall training phases of the training programs. TVET programs as suppliers and the employers as customers are so interrelated that the development of both must go forward hand in hand having practical partnership. The need to increase and strengthen the engagement of employers in TVET programs has been felt for many years in the country. However, employer engagement in the TVET programs of the Council for Technical Education and Vocational Training (CTEVT) is under-explored in Nepal. This article addresses the existing situation, explores issues, and shares some innovative initiations to strengthen the employer engagement in CTEVT technical schools.